Severe psychological distress among patients with epilepsy during the COVID‐19 outbreak in southwest China. (22nd May 2020) - Hao, Xiaoting; Zhou, Dong; Li, Zhe; Zeng, Guojun; Hao, Nanya; Li, Enzhi; Li, Wenjing; Deng, Aiping; Lin, Mintao; Yan, Bo
Abstract: Objective: To compare the severity of psychological distress between patients with epilepsy and healthy controls during the COVID‐19 outbreak in southwest China, as well as identify potential risk factors of severe psychological distress among patients with epilepsy. Methods: This cross‐sectional case‐control study examined a consecutive sample of patients older than 15 years treated at the epilepsy center of West China Hospital between February 1 and February 29, 2020. As controls, sex‐ and age‐matched healthy visitors of inpatients (unrelated to the patients) were also enrolled during the same period. Data on demographics and attention paid to COVID‐19 were collected by online questionnaire, data on epilepsy features were collected from electronic medical records, and psychological distress was evaluated using the 6‐item Kessler Psychological Distress Scale (K‐6). Potential risk factors of severe psychological distress were identified using multivariate logistic regression. Results: The 252 patients and 252 controls in this study were similar along all demographic variables except family income. Patients with epilepsy showed significantly higher K‐6 scores than healthy controls and spent significantly more time following the COVID‐19 outbreak (both P < .001). Univariate analyses associated both diagnosis of drug‐resistant epilepsy and time spent paying attention to COVID‐19 with severe psychological distress (defined as K‐6 score >12; both P ≤ .001). Multivariate logistic regression identified two independent predictors of severe psychological distress: time spent paying attention to COVID‐19 (odds ratio [OR] = 1.172, 95% confidence interval [CI] = 1.073‐1.280) and diagnosis of drug‐resistant epilepsy (OR = 0.283, 95% CI = 0.128‐0.623). Significance: During public health outbreaks, clinicians and caregivers should focus not only on seizure control but also on mental health of patients with epilepsy, especially those with drug‐resistant epilepsy. K‐6 scores > 12 indicate severe psychological distress. This may mean, for example, encouraging patients to engage in other activities instead of excessively following media coverage of the outbreak.